Efeitos protetores do Panax Ginseng C. A. Meyer sobre a genotoxicidade da doxorrubicina em células somáticas de Drosophila melanogaster - Pereira, Denise Gonçalves (2008)
Panax ginseng is one of the most widely prescribed herbal medicines for the treatment of cancer, diabetes, chronic inflammation, and neurodegenerative and cardiovascular diseases. Since the use of alternative medicines in combination with conventional therapy may increase the risk of unwanted interactions, we investigated the possible genotoxicity of a water-soluble form of the dry root of P. ginseng (2.5, 5.0 or 10.0 mg/mL) and its ability to protect against the genotoxicity of doxorubicin (DOX; 0.125 mg/mL) by using the Drosophila melanogaster wing somatic mutation and recombination test (SMART) with standard and high-bioactivation crosses of flies. Panax ginseng was not genotoxic at the concentrations tested, whereas DOX-induced genotoxicity in markerheterozygous flies resulted mainly from mitotic recombination. At low concentrations, P. ginseng had antirecombinogenic activity that was independent of the concentration of extract used. Recombination events may promote cancer, but little is known about the ability of P. ginseng to inhibit such recombination or modulate DNA repair mechanisms.